Importance-Performance Analysis on the Digital Platform Attributes of Food Convenience Store in Indonesia - Wahyudin, Moh.; Wuryandani, Shafira; Maksum, Mochammad; Arifadini, Qistina (Future Science / FSH-PH Publications, 2023)
The development of digital technology has changed many things in consumer behavior, including in shopping for daily necessities. The flexibility and efficiency offered by digital technology have encouraged the two largest retail companies in Indonesia to develop a digital food convenience store platform as a strategy to improve service to their customers. By 2021, the developed food convenience store platform has been used by more than one million customers. However, some customers have complaints against the platforms. It means that there are platform attribute performances that need to be improved. This study aims to analyze the attributes of the digital food convenience store platform that users consider important and contribute significantly to its performance. The number of respondents in this study was 200 users of digital food convenience stores platforms, and the data obtained were analyzed by the Importance Performance Analysis (IPA) method. As a result, there are 18 attributes that are considered extremely important by users: login methods, product diversity, user data security, delivery accuracy, product accuracy, customer service, shopping discount, shipping cost discount, direct delivery service and product compatibility. However, users rated that customer service, shopping discounts, and shipping discounts attribute did not meet their expectations. Overall, the performance of the digital food convenience store platform in Indonesia reached 85.83% of user expectations, so that the digital platform developer needs to concentrate on these three attributes so that the level of performance can be maximized and meet user expectations.